2005
DOI: 10.1152/ajplung.00224.2004
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of p42/p44 MAPK, p38 MAPK, JNK, and NF-κB in IL-1β-induced VCAM-1 expression in human tracheal smooth muscle cells

Abstract: Interleukin-1beta (IL-1beta) has been shown to induce the expression of adhesion molecules on airway epithelial and smooth cells and contributes to inflammatory responses. Here, the roles of mitogen-activated protein kinases (MAPKs) and nuclear factor-kappaB (NF-kappaB) pathways for IL-1beta-induced vascular cell adhesion molecule (VCAM)-1 expression were investigated in human tracheal smooth muscle cells (HTSMC). IL-1beta induced expression of VCAM-1 protein and mRNA in a time-dependent manner, which was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
66
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 54 publications
13
66
0
Order By: Relevance
“…In the present study, we showed that ERK, which is also a downstream signaling molecule of the VEGF pathway, is involved, at least in part, in this process. It has also been shown that the ERK signal transduction pathway is important in VCAM-1 expression (62). In the present study, our data show that hypoxiainduced VCAM-1 expression is diminished in IL-4 KO lungs, suggesting that IL-4 plays an important role in hypoxia-induced VCAM-1 expression and the subsequent inflammatory responses.…”
Section: Discussionsupporting
confidence: 74%
“…In the present study, we showed that ERK, which is also a downstream signaling molecule of the VEGF pathway, is involved, at least in part, in this process. It has also been shown that the ERK signal transduction pathway is important in VCAM-1 expression (62). In the present study, our data show that hypoxiainduced VCAM-1 expression is diminished in IL-4 KO lungs, suggesting that IL-4 plays an important role in hypoxia-induced VCAM-1 expression and the subsequent inflammatory responses.…”
Section: Discussionsupporting
confidence: 74%
“…The GRO-␣ promoter region contains NF-B DNA binding sites (14), and NF-B activation represents an important pathway mediating GRO-␣ secretion in several cell types, including ASMC. Both IL-1␤ and TNF-␣ stimulate NF-B activation in ASMC (15,16), and TNF-␣-induced expression of the chemokines, IL-8 and eotaxin, has been shown to be NF-B dependent (17,18). We have shown that GRO-␣ expression is dependent on the activation of NF-B because an inhibitor of the I B kinase complex that promotes the degradation of I B proteins and activates NF-B inhibited IL-1␤-and TNF-␣-induced GRO-␣ expression (5).…”
Section: Discussionmentioning
confidence: 98%
“…After washing twice with ice-cold PBS, cells were fixed, permeabilized, and stained using an anti-p65 or anti-Nrf2 Ab as previously described. 18 The images were observed using a fluorescence microscope (Zeiss, Axiovert 200M).…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%